2002
DOI: 10.1038/sj.bjc.6600419
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the sequential detection of circulating melanoma cells by RT–PCR in high-risk melanoma patients receiving adjuvant interferon

Abstract: The purpose of this study was to address the prognostic significance of circulating melanoma cells by reverse transcriptasepolymerase chain reaction in the peripheral blood of stage IIB and III melanoma patients on high-dose adjuvant interferon at multiple sequential time points from initiation of treatment. Tyrosinase mRNA in peripheral blood from these patients was assayed by reverse transcriptase polymerase chain reaction prior to initiation of adjuvant interferon, at completion of 1 month of intravenous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 15 publications
4
33
1
Order By: Relevance
“…The association between tyrosinase results and clinical outcome is also demonstrated by the early detection of disease recurrence after a positive determination. In our experience, this interval is lower (median 1.9 months) than that reported by Gogas (21 months) (Gogas et al, 2002), even if, according to the study design, follow-up investigations were anticipated only at the patients' request or due to clinical doubt, and not on the basis of tyrosinase results. The metastatic pattern of relapse, with a higher incidence of visceral localisations in positive than in negative patients, confirms that tyrosinase expression is significantly associated with the haematogenous metastatic pathway.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The association between tyrosinase results and clinical outcome is also demonstrated by the early detection of disease recurrence after a positive determination. In our experience, this interval is lower (median 1.9 months) than that reported by Gogas (21 months) (Gogas et al, 2002), even if, according to the study design, follow-up investigations were anticipated only at the patients' request or due to clinical doubt, and not on the basis of tyrosinase results. The metastatic pattern of relapse, with a higher incidence of visceral localisations in positive than in negative patients, confirms that tyrosinase expression is significantly associated with the haematogenous metastatic pathway.…”
Section: Discussioncontrasting
confidence: 62%
“…Mellado et al (2002) reported similar results in a cohort of 50 stage III patients treated with adjuvant IFN, showing positive results in 12% before treatment and 46% during follow-up. On the other hand, Gogas et al (2002) found a higher percentage of positive results before treatment (50%) in 60 stage IIB -III disease-free patients.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…at first presentation). In our work (Gogas et al, 2002), in 27 patients tested, one was already positive before operation becoming negative some time following operation' we would like to state that more than 95% of the patients referred to our Center have already been diagnosed with melanoma and require wide local excision, sentinel lymph node and consideration for adjuvant treatment. So, it was not possible to obtain blood from patients before any surgical manipulation.…”
Section: Sirmentioning
confidence: 94%
“…The paper published in Br J Cancer (2002, 87: 181 -186) on the prognostic significance of molecular detection of melanoma cells in melanoma patients under adjuvant interferon (Gogas et al, 2002) seems to be a continuation of the protocol we first applied in the same research laboratory utilizing the same facilities, the same methods and at least the same of some reagents (e.g. the ATTCC SK-mel-28 cells) we used in an analogous work.…”
Section: Sirmentioning
confidence: 99%